Do consumers prefer local animal products produced with local feed? Results from a Discrete-Choice experiment. (January 2019) - Profeta, Adriano; Hamm, Ulrich
Highlights: Do consumers prefer local feed for animal products labelled as 'local'? A survey and discrete choice experiment with 1602 consumers were conducted. High preferences and WTPs are evident for all food products with local feed. Animal products produced with local feed could open up a new market niche.